2011
DOI: 10.1001/archinternmed.2010.510
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Cognitive Behavioral Therapy vs Standard Treatment to Prevent Recurrent Cardiovascular Events in Patients With Coronary Heart Disease

Abstract: A CBT intervention program decreases the risk of recurrent CVD and recurrent acute myocardial infarction. This may have implications for secondary preventive programs in patients with coronary heart disease. Trial Registration clinicaltrials.gov Identifier: NCT00888485.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
206
0
23

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(233 citation statements)
references
References 27 publications
4
206
0
23
Order By: Relevance
“…251 In addition to the treatment of mood symptoms, there are several other approaches to psychosocial intervention that have proved useful. Two RCTs 252,253 have shown the favourable impact of stress management and social support groups on the prognosis of clinical CAD. Nurse-led interventions reveal beneficial effects on anxiety, depression and general well-being in CAD patients.…”
Section: Joint Esc Guidelinesmentioning
confidence: 99%
“…251 In addition to the treatment of mood symptoms, there are several other approaches to psychosocial intervention that have proved useful. Two RCTs 252,253 have shown the favourable impact of stress management and social support groups on the prognosis of clinical CAD. Nurse-led interventions reveal beneficial effects on anxiety, depression and general well-being in CAD patients.…”
Section: Joint Esc Guidelinesmentioning
confidence: 99%
“…11 Terminolojik açıdan bakıldığında, KR'de sunulduğu gibi, stres yönetimi için hasta çoğu zaman dinlenme (gevşeme) metotlarını da kapsayan çok bileşenli tedavilere yönlendirilir. 77 Araştırmalar hâlâ sınırlı olmasına rağmen, KVH'nin prognozunu iyileştirecek olan psikososyal girişimler için çok önemli olan stres yönetimi, vasküler endotelyal fonksiyon ve kardiyak otonomik kontrol gibi aterotrombotik hastalıklarda biyolojik mekanizmaları etkileyebilir. 78 CABG geçirmiş hastalarda depresyon ve öfkeyi azaltmanın yanı sıra, yaşam memnuniyetini de artırarak bir psikososyal beceri eğitimi girişiminin hem istirahatte hem de öfke sı-rasında KB'yi ve kalp hızını azalttığı görülmüş-tür.…”
Section: Psi̇kososyal Ri̇sk Faktörleri̇ni̇n Medi̇kal Tedavi̇ Yaklaşimiunclassified
“…[66,67]. Although stress management interventions with cardiac patients have successfully targeted potential triggers such as anger [28], overall there is currently no strong evidence for specific modes of prevention for acute stressors in individuals. In light of this, efforts to buffer the cardiovascular impact of acute stressors via health behaviours (e.g.…”
Section: Stress and Cvdmentioning
confidence: 99%
“…However, while a recent Cochrane review of psychological interventions for patients with CHD demonstrated small to moderate improvements in depression and anxiety with such interventions, there was no strong evidence that they reduced cardiac morbidity or mortality [70].Similarly, although encouraging results have been reported for interventions such as mindfulness-based stress reduction, TM, and yoga, overall these studies have been of low quality and thus no firm recommendations can be made for their ancillary use with cardiac populations [30; 71]. Stress management programmes most likely to be effective with cardiac populations should be multimodal, intensive, initiated only after the acute phase of illness has passed, delivered by appropriately trained clinicians and possibly should involve booster sessions after the intervention has been completed [72,28,73].…”
Section: Stress and Cvdmentioning
confidence: 99%
See 1 more Smart Citation